Mulheres escritas por mulheres : personagens femininas no romance brasileiro contemporâneo (2000-2014) - Doval, Camila Canali (2016)
This thesis confronts a corpus of Brazilian contemporary novels written by female authors with a feminist critiques research. The objective is to see if the female characters written by women have contributed to the women's empowerment project, observing the terms proposed by the Brazilian feminist movement and taking into account what it is inferred as a female perspective of the social world. For this, eleven female characters are analyzed, all them from ten novels published from 2000 to 2014, written by female authors born from the year 1970 that is considered the hallmark of feminism in Brazil.. The analysis division into two themes, the body and the spaces, which permeate the novels and are discussed by critics as fundamental to both the feminist project as for female authors of literature, made it possible to observe the female characters as a representation of contemporary women in a society still subject to the patriarchal order. The analysis dialogues with Brazilian researchers and the confrontation between the critical discourse produced by them and the fictional production that makes up the corpus of the research headed this work for the conclusion that most of the characters contemplated by this study also corresponds to the status quo defined by male authorship, subverting only part of the hegemonic context regarding to a reductive and even a stereotyped representations of women in the literature.